Econophysics applications to the Brazilian ethanol-sugar sector\'s prices - Quintino, Derick David (2022)
This thesis consists of an introductory chapter followed by two independent but related articles. The articles are situated under the same broader theme, namely, on the price relations of Brazilian hydrated ethanol, both from the point of view of relations with international prices and internal relations. The aim of Chapter 2 is to study whether Brazilian hydrous ethanol prices are correlated with carbon emission futures prices, compared to other potentially correlated international futures prices: oil and natural gas (the main commodities in the energy sector), as well as sugar (also produced from sugarcane by Brazilian mills).The Detrended Cross-Correlation Analysis (DCCA) method was used with sliding windows, in order to capture the correlations dynamically. The analysis comprised the period from January 2010 to July 2020. The results suggest that there is a significant correlation between ethanol and sugar and a moderate association with oil in the short term, but a weak and short-term relationship with carbon emission prices. Furthermore, in the dynamic analysis of sliding windows, the strength of the correlation between ethanol and emission prices ranges from weak to not significant. Chapter 3, in its turn, aims to analyze the degree of persistence of the relative prices of hydrated ethanol gasoline C, considering 15 Brazilian capitals located in the 5 major regions of the country. It also analyzes the degree of correlation of relative prices between São Paulo, capital of the main producer and consumer state of hydrated ethanol, compared to other capitals. The analyzed period is between May 2004 and December 2020. The DFA (Detrended Fluctuation Analysis) and DCCA methods are used to investigate the degree of persistence and correlation, respectively, using sliding windows. It was found that the degree of persistence varies according to the location of the analyzed capital, which suggests specific local dynamics of relative prices. As for the correlations, these also suggest that the estimates are dependent on the location of the capitals, so that regions that are more geographically distant from São Paulo exhibit a lower correlation degree of relative prices. This suggests a regionalized vis-à-vis unified character of convergence of national relative prices.